Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Paket Wisata di Oma Tour & Travel - Aidnilla Sinambela, Fitriana; Wirawan, Adhitomo (GEMA EKONOMI, 2023)
The purpose of this study was to determine the effect of the marketing mix on the decision to purchase tour packages at OMA tour & travel. This study used an explanatory research method with 87 OMA tour & travel customers throughout Indonesia. From the results of multiple regression, it shows that there is a partial effect on the product variable on the decision to purchase a tour package at OMA tour & travel of 0.385, there is a partial effect on the promotion variable on the decision to purchase a tour package at OMA tour & travel of 0.134, a partial effect on the place variable on the decision to purchase a tour package at OMA tour & travel is 0.192, the partial effect of the price variable on the decision to purchase a tour package at OMA tour & travel is 0.496 and there is a partial effect on the process variable on the decision to purchase a tour package at OMA tour & travel travel of 0.269. As for the variables of people and physical evidence, there is no partial effect on the decision to purchase a tour package at OMA tour & travel. There is a simultaneous influence on product, promotion, place, price, people, process and physical evidence variables on the decision to purchase a tour package at OMA tour & travel